Implementation of Management Information Systems in Monitoring Creative Economic Development - Husain Ali; Abdul Hadi Sirat; Ida Nurhaida (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The Central Halmahera Regency Government has established a Management Information System to enhance service provision across various sectors. A primary focus is the creative economy, which is rapidly evolving alongside the designation of this region as a national strategic industrial area. The development of the creative economy in Central Halmahera emphasizes enhancing competitiveness, improving the capacity of human resources for creative economy stakeholders, strengthening digital-based creative enterprises, and promoting comprehensive digital transformation. This study aims to assess the implementation of the management information system in monitoring the creative economy's development and to identify the challenges encountered during this implementation. Employing a descriptive qualitative methodology, data collection involved direct interviews, observations, and documentation studies to gather both primary and secondary data. The findings indicate that the implementation of the management information system in Central Halmahera is suboptimal, primarily due to insufficient telecommunications infrastructure support at the village level and a lack of digital literacy among stakeholders. Although the relevant Regional Apparatus Organizations have established websites as digital platforms for monitoring the creative economy, systematic and integrated monitoring based on information technology has yet to be achieved. There is a pressing need to enhance the monitoring of the creative economy by developing a digital-based monitoring system. The regional government must devise an appropriate scheme and framework to create an integrated Management Information System that streamlines the collection of levies, thereby enabling this sector to contribute to the enhancement of regional financial capacity through the optimization of Regional Original Income.